The Impact of Employee Competence, Employee Training, and Human Resource Development on Employee Performance Mediated by Employee Performance at Insurance Company X - Putrapandowo, Habie Purwokusumo; Meilani, Yohana F. Cahya Palupi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
In an era of increasingly fierce competition, human resources (HR) are crucial to a company's success. Competence, training, and HR development are important elements in improving employee performance. A positive work culture also significantly contributes to employee performance. Insurance Company X, facing challenges in meeting performance targets, is committed to improving HR quality through training and cultivation. Through Insurance Company X's work culture, the purpose of this study is to inspect how employee competence, employee training, and human resource development affect employee performance. The permanent employees of Insurance Company X serve as the unit of analysis in this quantitative study. Data were obtained through an online questionnaire filled out by 136 permanent employees. Data analysis was conducted using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The findings stated that employee competence, employee training, human resource development, work culture have a significant and positive impact on employee performance. By focusing on improving competence, HR development, training, and a good company work culture, the company can ensure that employees are ready to face existing challenges and provide maximum contribution to achieving organizational goals. This study combines four key variables-competence, training, HR development, and work culture in one framework to analyze their influence on employee performance in the insurance industry. The results of this study can be used by management to design strategies to improve employee performance through structured training, competency improvement, continuous HR development, and strengthening a positive work culture that supports productivity and achievement of organizational targets.